Discovery of granulocyte-lineage cells in the skin of the amphibian Xenopus laevis - Kelsey Hauser; Milan Popovic; Amulya Yaparla; Daphne V. Koubourli; Phillip Reeves; Aashish Batheja; Rose Webb; María J. Forzán; Leon Grayfer (Canadian Science Publishing, 2020)
The ranavirus Frog Virus 3 (FV3) and the chytrid fungus Batrachochytrium dendrobatidis (Bd) are significant contributors to the global amphibian declines and both pathogens target the amphibian skin. We previously showed that tadpoles and adults of the anuran amphibian Xenopus laevis express notable levels of granulocyte chemokine genes (cxcl8a and cxcl8b) within their skin and likely possess skin-resident granulocytes. Presently, we show that tadpole and adult X. laevis indeed possess granulocyte-lineage cells within their epidermises that are distinct from their skin mast cells, which are found predominantly in lower dermal layers. These esterase-positive cells responded to (r)CXCL8a and rCXCL8b in a concentration- and CXCR1/CXCR2-dependent manner, possessed polymorphonuclear granulocyte morphology, granulocyte marker surface staining, and exhibited distinct immune gene expression from conventional granulocytes. Our past work indicates that CXCL8b recruits immunosuppressive granulocytes, and here we demonstrated that enriching esterase-positive skin granulocytes with rCXCL8b (but not rCXCL8a) may increase tadpole susceptibility to FV3 and adult frog susceptibility to Bd. Furthermore, pharmacological depletion of skin-resident granulocytes increased tadpole susceptibility to FV3. This manuscript provides new insights into the composition and roles of immune cells within the amphibian skin, which is a critical barrier against pathogenic contributors to the amphibian declines.